Strategi Pembelajaran Untuk Mengembangkan Keterampilan Sosial Emosional Anak Usia Dini - Khadijah Khadijah; Rizka Khairi; Hairani Ananda Putri; Herlin Syahdina Lubis; Melvi Sari Anggraini; Fadhila Husna; Rika Nazwa Sabila (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
There are several aspects of development in early childhood, namely one aspect that needs to be stimulated in early childhood is the aspect of social emotional development. The way to develop social emotional skills in early childhood is to implement the right strategy. The aim of this research is to find out what strategies are appropriate to implement with young children in learning. The data sources in this research are teachers and early childhood. The method used in this research is a qualitative method. The technique used in this research is literature study. The research results show that there are many strategies that can be used in learning to develop the social emotional skills of early childhood, with the teacher's ability to implement these strategies in learning by adjusting the abilities of each student (early childhood). If the strategies given are correct, the social emotional skills of young children will also be able to develop optimally.